MANAJEMEN PENDIDIKAN MULTIKULTUR DAN AKTUALISASI ISLAM MODERAT DALAM MEMPERKOKOH NASIONALISME DI INDONESIA - Subandi Subandi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2018)
The purpose of this study is to describe the management of multicultural education in instilling the value of Indonesian culture through learning in educational institutions to cultivate and instill a variety of cultures, religions and Indonesia, this is an engineering or developmental ideas in learning from the age of elementary school to university, so as to be able to provide the basis of national values ​​(nationalism), tolerance and not thinking and acting radically. This research is a field research with a descriptive qualitative approach with a tool to collect observation data, interviews from several key informants and analyze them with inductive thinking. The development of multicultural education in fostering a spirit of nationalism, and radicalism in radicalism, is carried out through: 1. Integrating moderate Islam by planting the attitudes of tawassuth, tassamuh, and tawazun, 2. Introducing the environment around as plural learning (contectual learning), 3. Instill the attitude of anti-violence truth rahmatan lil alamin These three things as engineering application of material development, are thoroughly integrated in the learning process in the classroom and outside the classroom. Conclusion, Education is carried out programmatically while: 1). Transformation of knowledge through the understanding of contemporary Islam, 2). Adopt good culture (repertoire), 3). Acting in the educational environment with the attitudes of tawassuth, tassamuh and tawazun, amar ma'ruf nahimunkar anti violence 4) Performed in the form of behavior and developing tepo seliro tolerant concepts on all learning processes and 5) Character of nationalism in life (Khoirunas Anfauhum Linnas) . The impact that arises in a timely manner recognizes moderate Islam, fosters the development of nationalism fostering a sense of love for the land as a manifestation of the preservation of Islam rahmatan lil alamin and strengthening the unity of the Indonesian nation.